Integrating rights and evidence: a technical advance in abortion guideline development. Issue 2 (8th February 2021) - de Londras, Fiona; Cleeve, Amanda; Rodriguez, Maria Isabel; Lavelanet, Antonella
Abstract : As part of its core work, the WHO generates, translates and disseminates knowledge, including through guideline development. In recent years, substantial work has been undertaken to revise the Evidence to Decision framework in order to fully integrate inter alia human rights. This paper describes an innovative methodological approach taken by the authors to inform law and policy recommendations for the forthcoming third edition of the Safe Abortion: Technical and Policy Guidance for Health Systems. The methodology described here effectively integrates human rights protection and enjoyment as part of health outcomes and analysis, ensuring that subsequent recommendations are consistent with international human rights standards. This will allow guideline users to make informed decisions on interventions, including legal and policy reform, to fulfil relevant human rights including the right to health.